Loss minimization in a multihoming vehicular network - Gomes, Christian Anjos (2018)
The growing interest in Vehicular Ad-hoc NETworks (VANETs) is encouraging its deployment in new environments, allowing the development of safety and entertainment applications. Vehicles can connect to other vehicles or to the infrastructure, providing an Internet connection. The communication equipment placed inside the vehicles may have multiple network interfaces of diverse technologies, such as IEEE 802.11p/WAVE, IEEE 802.11a/g/n (Wi- Fi) and cellular. This diversity enables the exploration of Multihoming (MH) and Network Coding (NC) mechanisms which can be used to provide higher bandwidth and reliability to these services, reducing packet losses due to poor wireless signal quality, therefore improving the final Quality-of-Service (QoS). This dissertation enhances the communication quality of a MH vehicular network by improving its mobility protocol and the NC mechanisms. Specifically, changes were performed to ensure the reliability of control mobility messages to help the infrastructure to react faster to the wireless communication conditions of a mobile node. On a different perspective, it has been provided a mechanism to enable NC through different technologies being used in MH, and making use of all technologies simultaneously to code and recover the packets. Both approaches were evaluated with real systems in a laboratory scenario. The obtained results on the reliability of the control messages show that the new approach is able to provide higher communication reliability, reducing the packet losses presented in case of an abrupt disconnection, and when in presence of other connections. For the multi-technology architecture proposed for the NC, the experimental tests evaluated its impact on the effective delivery ratio and the delay. The comparative results show that the multi-technology approach integrated with MH has a better delivery ratio when compared to the single-technology, despite the small impact on the packet delay.